Short-Term Effectiveness of Ultrasound Treatment in Patients with Lateral Epicondylitis: Randomized, Single-Blind, Placebo-Controlled, Prospective Study - Ceyda Akın,; Öznur Öken,; B. Füsun Köseoğlu, (Archives of Rheumatology, 2010)
Objective: We aimed to assess the effectiveness of ultrasound treatment in patients with lateral epicondylitis and to compare with placebo ultrasound treatment. Materials and Methods: Sixty patients (40 female, 20 male, mean age±SD 46.7±8.1, range 25-62) with lateral epicondylitis were included. All of the patients were randomized to two groups as: ultrasound (US) group (n=30) and placebo US group (n=30). Continuous US was applied to the patients in the US group whereas placebo US was applied to those in the placebo group for 5 minutes over three weeks (totally 15 sessions). All patients used a static splint at night for the three weeks. Patients were assessed before the treatment (baseline), at the end of the treatment (3rd week) and after 15 days follow-up (5th week). The following parameters were evaluated: pain with the visual analog scale (VAS), hand grip strength using a hand dynamometer, activities of daily living using the Turkish version of Disabilities of the Arm, Shoulder and Hand (DASH-T) questionnaire, and quality of life using the Short-Form (SF)-36 questionnaires. In addition, patient satisfaction was examined. Results: VAS at rest and during motion had significantly improved in both groups at the end of treatment (3rd week) and in the follow-up (5th week), while improvement in the VAS was observed only in the 3rd week in placebo group (p<0.01). Pain with motion was significantly decreased in the 3rd and 5th weeks in the US group while it was increased in the 5th week in the placebo group (p<0.01). Hand grip strength were improved in the 3rd and 5th weeks in both groups (p<0.008). There was no significant difference between the two groups (p>0.05). No difference between the two groups was found in terms of general DASH-T scores at the end of the treatment and follow-up. However, improvement in DASH scores in the US group at the 3 rd and 5 th weeks was significantly higher than in the placebo group (p<0.017). Patient satisfaction scores increased in both groups, but satisfaction of patients in the US group was significantly higher than of those in the placebo group (p<0.001). Conclusion: In this study, it was found that US treatment for lateral epicondylitis improved pain and activities of daily living and resulted in high patient satisfaction. (Turk J Rheumatol 2010; 25: 50-5)